Comparison of 3He and 129Xe MRI for evaluation of lung microstructure and ventilation at 1.5T. Issue 3 (5th March 2018) - Stewart, Neil J.; Chan, Ho‐Fung; Hughes, Paul J.C.; Horn, Felix C.; Norquay, Graham; Rao, Madhwesha; Yates, Denise P.; Ireland, Rob H.; Hatton, Matthew Q.; Tahir, Bilal A.; Ford, Paul; Swift, Andrew J.; et al.
Abstract : Background: To support translational lung MRI research with hyperpolarized 129 Xe gas, comprehensive evaluation of derived quantitative lung function measures against established measures from 3 He MRI is required. Few comparative studies have been performed to date, only at 3T, and multisession repeatability of 129 Xe functional metrics have not been reported. Purpose/Hypothesis: To compare hyperpolarized 129 Xe and 3 He MRI‐derived quantitative metrics of lung ventilation and microstructure, and their repeatability, at 1.5T. Study Type: Retrospective. Population: Fourteen healthy nonsmokers (HN), five exsmokers (ES), five patients with chronic obstructive pulmonary disease (COPD), and 16 patients with nonsmall‐cell lung cancer (NSCLC). Field Strength/Sequence: 1.5T. NSCLC, COPD patients and selected HN subjects underwent 3D balanced steady‐state free‐precession lung ventilation MRI using both 3 He and 129 Xe. Selected HN, all ES, and COPD patients underwent 2D multislice spoiled gradient‐echo diffusion‐weighted lung MRI using both hyperpolarized gas nuclei. Assessment: Ventilated volume percentages (VV%) and mean apparent diffusion coefficients (ADC) were derived from imaging. COPD patients performed the whole MR protocol in four separate scan sessions to assess repeatability. Same‐day pulmonary function tests were performed. Statistical Tests: Intermetric correlations: Spearman's coefficient. Intergroup/internuclei differences: analysis of variance / Wilcoxon's signed rank. Repeatability: coefficient of variation (CV), intraclass correlation (ICC) coefficient. Results: A significant positive correlation between 3 He and 129 Xe VV% was observed ( r = 0.860, P < 0.001). VV% was larger for 3 He than 129 Xe ( P = 0.001); average bias, 8.79%. A strong correlation between mean 3 He and 129 Xe ADC was obtained ( r = 0.922, P < 0.001). MR parameters exhibited good correlations with pulmonary function tests. In COPD patients, mean CV of 3 He and 129 Xe VV% was 4.08% and 13.01%, respectively, with ICC coefficients of 0.541 ( P = 0.061) and 0.458 ( P = 0.095). Mean 3 He and 129 Xe ADC values were highly repeatable (mean CV: 2.98%, 2.77%, respectively; ICC: 0.995, P < 0.001; 0.936, P < 0.001). Data Conclusion: 129 Xe lung MRI provides near‐equivalent information to 3 He for quantitative lung ventilation and microstructural MRI at 1.5T. Level of Evidence : 3 Technical Efficacy Stage 2 J. Magn. Reson. Imaging 2018;48:632–642.